Community structure of makrozoobenthos in swamp area of the Sawah Village, Kampar Regency, Riau - Harahap, Masdalifa; Fajri, Nur El; Adriman, Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTIn the swamp area of the Sawah village, there are settlements, agriculture and farms that flew their liquid waste to the swamp and polluting that area. To understand the water quality of the swamp based on macrozoobenthos community, a research was conducted in March-April 2018. The method used is survey method.The location of the sampling is determined using purposive sampling. Samples taken with PVC pipe ( 7 cm diameter), then it was sieved and sorted by hand. Captured macrozoobenthos was preserved with formalin 10%.Parameters measured were the abundance, diversity index, dominance index, and uniformity index. Water quality parameters measured were temperature, transparency, depth, pH, and dissolved oxygen.There were 3 stations and in each station, there were 3 sampling points. Macrozoobenthos and water were sampled 3 times, once/week. Result shown that there were 4 types of macrozoobenthos present, namely Annelids (Hirudo sp.), crustaceans(Macrobachium sp.), insects(Ablesmyia sp.) and oligochaete(Lumbricus sp.). The abundance of macrozoobenthos ranged from 59 -113 organisms/m2, diversity index was 0.930-1.740, dominance index was 0.651–0.3524, and uniformity index was 0.588–0.870. The water quality parameters were as follow: temperature 29 – 30 0C, transparency 57- 62 cm, depth 1.22-0.97 m, pH  5 and dissolved oxygen 4.7-4.5 mg/L. Data obtained indicate that the water of the Sawah Village is moderately polluted.Keywords :swamporganism, swamp pollution, diversity index, purposive sampling